(3QSGdI PcQ eYQaI GdEeGe hCSeGFg GdYdhjI QhMGfi hLSeGfis - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce GdeYHhO hEdjg CTQfG HGdhMOGfjI ai SGFQ GdOghQ GdCSeGA GdhGbYI Ydi ehdGi bGFe GdReGf GdChd efgG YdI GdYdd s
(3BNQgG (B:s
(3SajQ GdbOQI GdLfGM GdCjef GdLfGM GdCjSQ CdbGHge GdeLJHi UahI GdeSJLjHjf hGdMeO dehdGfG Edg GdYGdejf JeJ hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B33s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds